2016
DOI: 10.1242/dmm.022558
|View full text |Cite
|
Sign up to set email alerts
|

Tau excess impairs mitosis and kinesin-5 function, leading to aneuploidy and cell death

Abstract: In neurodegenerative diseases such as Alzheimer's disease (AD), cell cycle defects and associated aneuploidy have been described. However, the importance of these defects in the physiopathology of AD and the underlying mechanistic processes are largely unknown, in particular with respect to the microtubule (MT)-binding protein Tau, which is found in excess in the brain and cerebrospinal fluid of affected individuals. Although it has long been known that Tau is phosphorylated during mitosis to generate a lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 67 publications
2
30
1
Order By: Relevance
“…It has been recently reported that 4R-Tau over expression in Drosophila wing discs induces a mitotic delay characterized by the formation of monopolar spindles leading to aneuploidy and cell death in a non-neuronal cell context9. In addition, the authors observed a similar spindle phenotype within the larval neuronal progenitors but without further investigation.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been recently reported that 4R-Tau over expression in Drosophila wing discs induces a mitotic delay characterized by the formation of monopolar spindles leading to aneuploidy and cell death in a non-neuronal cell context9. In addition, the authors observed a similar spindle phenotype within the larval neuronal progenitors but without further investigation.…”
Section: Resultsmentioning
confidence: 92%
“…Third, in mice, expression of similar Tau mutations also induces genomic instability ranging from chromosome rearrangements to aneuploidy8. Finally, a recent report showed that human Tau overexpression in Drosophila can induce a mitotic block leading to aneuploidy9.…”
mentioning
confidence: 99%
“…Accordingly, a recent study found that tau can also inhibit Eg5 activity; thus, Ab may inhibit Eg5 not only directly but also indirectly via regulation of tau (Bougé and Parmentier, 2016). Overall, it is likely that there is very complex interplay between Ab, tau, and Eg5 in the regulation of neuronal function, which definitely warrants future investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, increased level of aneuploidy in splenic lymphocytes of tauopathy transgenic mouse models have recently been reported (Rossi et al, 2014). In Drosophila, human Tau excess impairs mitosis, leading to aneuploidy and cell death (Bouge and Parmentier, 2016). Plausibly, abnormal activation of SRPK2 may phosphorylate numerous substrates including delta-secretase, Tau, SR domain containing splicing factors, coordinating the AD pathologies, coupling defective cell cycle machinery to neuronal cell death.…”
Section: Discussionmentioning
confidence: 99%